Media Online dan Perkembangannya - Winda Kustiawan; Dama Kania Harahap; Nurul Ainun Jannah; Waldi Afalah Sinaga; Nurfatin Safika; Hadromi Alwi Lubis; Ahlan Adib Al Barry (Prodi Perpustakaan dan Sains Informasi, 2022)
The media is currently developing rapidly, especially online media or the internet. This online media began to grow rapidly around the 1990s, at that time in the form of a program. This program is called www or the World Wide Web which is growing very rapidly due to the increasing need for information. This article uses a qualitative approach with a literature study method to find out how online media is developing. The beginning of the emergence of online media was marked by the emergence of the World Wide Web (WWW) which was created by Tim Berners Lee in 1989. This made other media use the internet. Four years later, in 1993, to be precise, the University of Florida released a website on journalism that sparked other newspapers to join the internet. In Indonesia, the internet began to be widely known by the public in 1994 due to the emergence of commercial internet services, namely Indonet. In the same year, the first imedia appeared on the internet, namely Republika Online (www.replubika.co.id) on August 17, 1994. Then other online news sites began to appear, such as www.tempo.co, www.waspada.co.id , to www.kompas.com.